Strengths-based Programming for First Nations Youth in Schools: Building Engagement Through Healthy Relationships and Leadership Skills - Crooks, Claire V.; Chiodo, Debbie; Thomas, Darren; Hughes, Ray (International Journal of Mental Health and Addiction, 2010)
FirstNationsyouthinCanadademonstratedisproportionatelyhighratesofnegative behaviors such as violence, substance abuse, and leaving school early. An understanding of historical context and current environment helps explain these patterns. Providing culturally relevant opportunities for youth to build healthy relationships and leadership skills has the potential to increase youth engagement. Over the past four years our multidisciplinary team of researchers, educators, program developers, and community leaders have worked together to develop a number of school-based initiatives that focus on increasing youth engagement through building on strengths and the promotion of healthy relationships. Specific strategies include peer mentoring, a credit-based academic course, and transition conferences for grade 8 students. This article describes these initiatives and some of the early successes and challenges we have faced in the design and implementation of them. Preliminary evidence is presented to support the contention that these initiatives increase youth engagement.